Commentary : rejecting psychological eloquence through figure paintings / Nur Azeema Suhaimi - Suhaimi, Nur Azeema (Universiti Teknologi MARA, Perak, 2019)
Beauty is one of the most mysterious commodities. The idea of “beautiful” itself varied across cultures and keep changing over time (Fallon, 1990). In this century of shifting relations and alliances between despotic rulers, the portrait had its diplomatic function. Besides providing a reminder at home to officials and courtiers of the governing power, the ruler-image was a symbol of international exchange while, the artist himself an international figure. This writing intended as a response on women and beauty standards that has been reflected by the artist through her paintings.